Asteroids were born bigger: An implication of surface mass ablation during gas-assisted implantation into the asteroid belt - Ribeiro de Sousa, Rafael [UNESP]; Izidoro, Andre; Deienno, Rogerio; Dasgupta, Rajdeep (Elsevier, 2024)
The origins of carbonaceous asteroids in the asteroid belt is not fully understood. The leading hypothesis is that they were not born at their current location but instead implanted into the asteroid belt early in the Solar System history. In this study, we investigate how the migration and growth of Jupiter and Saturn in their natal disk impact nearby planetesimals and subsequent planetesimal implantation into the asteroid belt. Unlike traditional studies, we account for the effects of surface ablation of planetesimals caused by thermal and frictional heating between the gas-disk medium and planetesimal surface, when planetesimals travel through the gas disk. We have performed simulations considering planetesimals of different compositions as water-ice rich planetesimals (composed of more than 80% water by mass), water-ice poor planetesimals (relatively dry and enstatite-like), organic-rich planetesimals, and fayalite-rich planetesimals. Our findings indicate that, regardless of the migration history of the giant planets, water-ice rich, organic-rich, and fayalite-rich planetesimals implanted into the asteroid belt generally experience surface ablation during implantation in the asteroid belt, shrinking in size. On the other hand, planetesimals with enstatite-like compositions were inconsequential to surface ablation, preserving their original sizes. By assuming an initial planetesimal size-frequency distribution (SFD), our results show that – under the effects of surface ablation – the planetesimal population implanted into the asteroid belt shows a SFD slope slightly steeper than that of the initial one. This holds true for all migration histories of the giant planets considered in this work, but for the Grand-Tack model where the SFD slope remains broadly unchanged. Altogether, our results suggest that the largest C-type asteroids in the asteroid belt may have been born bigger. High-degree surface ablation during implantation into the asteroid belt may have even exposed the cores of early differentiated C-type planetesimals.
Keywords: Asteroid belt; Asteroids; Protoplanetary disk interactions; Solar system; Surface mass ablation